Controlled coculture fermentation for the production of new beverages - Bader, Johannes; Mast-Gerlach, Edeltraud; Stahl, Ulf (BrewingScience, 2007)
Special strains of Gluconobacter, Lactobacillus and Kluyveromyces have been selected for the production of a new beverage on the basis of wort. This beverage contains the health benefiting substances gluconic acid, lactic acid and an ethanol concentration below 0.5 % (v/v). Fermentation was adapted for growth behaviour and to maximise production – the strategy developed concurrently produces (a) gluconic acid by using the strictly aerobic Gluconobacter strain and (b) lactic acid by using the anaerobic strain of Lactobacillus. The concentrations of the simultaneously produced organic acids are controlled by the level of oxygen in the fermentation medium. The following mixed fermentation of Lactobacillus, Gluconobacter and Kluyveromyces using the chosen yeast strain resulted in producing a pleasant flavour.